2022
DOI: 10.3390/ijerph192316201
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Evaluation of Emergency Management Capacity of Resilient Communities by the AHP-TOPSIS Method

Abstract: Community emergency management is directly related to the safety of people’s lives and properties and is concerned with economic development and social stability. This paper established an evaluation model of community emergency management capacity from the perspective of resilience based on hierarchical analysis (AHP) and distance between superior and inferior solutions (TOPSIS). In terms of infrastructure resilience, community organizational resilience, risk, and hidden danger management, emergency material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“… Step 2: Perform a pairwise comparison for each layer to compare the weights of each element. Using a score from 1 to 9, which is the basic scale of the AHP, each pair is compared according to the expert’s judgment, and the importance is judged [ 19 , 20 ]. …”
Section: Methodsmentioning
confidence: 99%
“… Step 2: Perform a pairwise comparison for each layer to compare the weights of each element. Using a score from 1 to 9, which is the basic scale of the AHP, each pair is compared according to the expert’s judgment, and the importance is judged [ 19 , 20 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Dzigbede et al ( 25 ) utilized an item response theory (IRT) model to categorize and delineate the concept of community resilience across four dimensions: capacity, attributes, structure, and processes, thereby establishing a theoretical model for community resilience assessment. Wang et al ( 26 ), utilizing fuzzy analytic hierarchy process (FAHP) and fuzzy Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), developed a model for assessing community risk factors in the context of the COVID-19 pandemic. Using four communities as case studies, they quantified 12 evaluation indicators, including suspected infection, confirmed number, isolation of relevant personnel, enclosure and closure, and the establishment of unified entrances and exits, etc., resulting in safety risk values and relative rankings for the case study communities.…”
Section: Related Workmentioning
confidence: 99%
“…The level of urban emergency response capacity directly affects the ability of urban systems to respond to disasters [35]. Therefore, this thesis reflects the comprehensive emergency management capability in terms of grassroots prevention construction, safety and governance capability, social supervision services, press and publicity situation, and organization and institution construction [36,37].…”
Section: Construction Of the Evaluation Systemmentioning
confidence: 99%